FACTORS INFLUENCING EMPLOYEE SATISFACTION IN STAFFING FIRMS (International Journal of Food and Nutritional Sciences, 2023)
As employee engagement directly drives client satisfaction within staffing organizations, it is especially pivotal that the workforce approves of internal organizational policies. This investigation highlights what really drives job satisfaction for staffing firm employees, across work environment, compensation, opportunities for advancement, leadership style, work-life balance, and organizational culture. Using a mixed-methods approach, combining quantitative surveys with qualitative interviews of staffing company employees, researchers studied to determine levels of job satisfaction and underlying explanations for perceived satisfaction with work. Discover findings that show competitive reimbursement, communication transparency and career growth prospects significantly increase satisfaction among employees. On the contrary, high workload requirements and lack of job security act as significant repellents. Staffing companies should strategically deploy human resource practices that create a supportive climate and promote satisfaction which leads to employee retention and productivity, the analysis highlights.